(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to find out the symbolic meaning of Pa’bitte Passapu Dance in Kajang District, Bulukumba Regency This research was analyzed rely on Ferdinand de Saussure’s theory of markers and signs. The research applies qualitative methods and uses a semiotic approach to analyze the data. Researchers use observation, interviews, and documentation as instruments to present valid data. The findings suggest that they are four types for analyzing Pa’bitte passapu such as movements, songs, instruments, costumes and accessories. The results of this study show the meaning of the symbol of each movement of Pa’bitte Passapu Dance in Kajang District, Bulukumba Regency, not only movements but also musical instruments and costumes in the dance. Pa’bitte Passapu dance is from Kajang District, Bulukumba Regency. Pa’bitte Passapu dance is one of the most developed dances in the region, in addition to the annete panne dance in the attahuru ritual which is often performed by the regional community.